Impaired Development of Early Endometriotic Lesions in CD44 Knockout Mice. (January 2016) - Knudtson, Jennifer F.; Tekmal, Rajeshwar R.; Santos, Marlen Tellez; Binkley, Peter A.; Krishnegowda, Naveen; Valente, Philip; Schenken, Robert S.
Previous studies have shown endometrial cell (EC) CD44 and peritoneal mesothelial cell (PMC)-associated hyaluronan (hyaluronic acid [HA]) are involved in the attachment of endometrial stroma and epithelial cells to peritoneal mesothelium. Here we assess the CD44–HA interaction in the formation of the early endometriotic lesion using CD44 –/– (knockout) mice. Using an established murine model and crossover technique, endometrial tissue from donor mice (wild type [WT] and CD44 –/– ) was used to induce endometriosis in recipient mice (WT and CD44 –/– ). Endometriotic lesions were visualized by fluorescent microscopy and confirmed by hematoxylin and eosin staining. Early endometriotic lesions were decreased when CD44 –/– endometrium was placed in WT recipients and when WT endometrium was placed in CD44 –/– recipients ( P = .002). Early endometriotic lesions were also significantly decreased when both peritoneal and endometrial tissues lacked CD44 expression ( P < .01). These studies demonstrate that both EC and PMC CD44 play a role in the development of early endometriotic lesion.